Use of Disinfection Chamber to Prevent Covid-19 at the Faculty of Veterinary Medicine, Universitas Airlangga - Warsito, Sunaryo Hadi; Mufasirin, Mufasirin; Yunus, Muchammad (Jurnal Medik Veteriner, 2021)
Community empowerment at the Faculty of Veterinary Medicine and Animal Education Hospital (RSHP) Universitas Airlangga aimed to prevent Covid-19 among students, picket workers, employees, veterinarians, nurses, and the client who bring animals to RSHP. The program starts from observation to implementation in May-October 2020. Implementation of community empowerment program in collaboration with the KKN program in Surabaya. This program introduced the disinfection chamber model of an automatic sprayer that is safe for health and complies with the standard operating procedure (SOP) for the use of the disinfection chamber. The existence of a disinfection chamber at the entrance to the campus and RSHP has contributed a lot to prevent the spread of Covid-19. The post-test results showed an increase in public understanding of the existence of disinfection chamber as a way to reduce the spread of Covid-19 and implement health protocols and healthy lifestyles.